Dinamika Kecemasan pada Istri Prajurit dalam Pernikahan Jarak Jauh: Anxiety Dynamics in Military Long Distance Marriage Wives - Chory Ayu Rahmadani; Ramon Ananda Paryontri (Academia Open, 2025)
This study discusses psychological conditions experienced by wives in military long-distance marriages. General Background: Long-distance marriage has become a growing social phenomenon that presents emotional and psychological challenges within family systems. Specific Background: Wives of military personnel face prolonged separation due to assignments in conflict-prone areas, which may trigger anxiety and emotional instability. Knowledge Gap: Previous studies have examined marital conflict and coping strategies, yet limited attention has been given to in-depth qualitative exploration of anxiety dynamics among military wives in this specific context. Aims: This study aims to analyze the forms, sources, and psychological processes of anxiety experienced by wives whose husbands are assigned to remote or conflict areas. Results: The findings indicate that anxiety emerges through emotional distress, fear of uncertainty, and concerns about safety, while social support and religiosity contribute to psychological adjustment. Novelty: This study provides contextualized qualitative evidence highlighting internal emotional processes and adaptive mechanisms among military wives in long-distance marriages. Implications: The findings contribute to family psychology literature and provide a foundation for developing psychosocial support interventions for military families. Keywords: Long Distance Marriage, Anxiety, Military Wives, Family Psychology, Social Support Key Findings Highlights: Emotional distress and uncertainty characterize psychological responses during spousal deployment. Religious coping and social networks support personal adjustment processes. Contextual qualitative data reveal internal experiences within military family systems.